Analisis Kepuasan Pengguna Terhadap Aplikasi Spotify Menggunakan Metode End User Computing Satisfaction (EUCS) - M Ferlian Sijadah; Nabila Rizky Oktadini; Allsela Meiriza; Pacu Putra; Putri Eka Sevtiyuni (STMIK Pringsewu, 2023)
Music streaming applications are applications that allow users to listen to legal or online music. Spotify is currently known as the application that provides the largest music streaming service, digital music, podcast, and video service with access to millions of songs and other content from various creators worldwide. This research concerns the analysis of user satisfaction with the Spotify application. This research was conducted to understand and determine user satisfaction with the Spotify application. The method used in this research is End User Computing Satisfaction (EUCS). There are also problems with this music application related to the competition system when listening to music online. The sampling technique uses Lemeshow sampling (based on coincidence) with a total of 100 respondents using a research instrument in the form of a questionnaire using a Likert scale, which is a scale used to measure perceptions, attitudes, or opinions of users towards the Spotify application. shows that the level of user satisfaction from the five variables shows that the Content variable gets the highest satisfaction with a total percentage of 78.5%, the Accuracy variable gets high satisfaction with a total percentage of 77.5%, the Format variable gets the highest satisfaction with a total percentage of 79.9%, the Variable Ease of Use gets high satisfaction with a percentage of 84.6%, the Timelines variable gets high satisfaction with a percentage of 78.9%.